ExRNA - Zhang, Chen-Yu; Zen, Ke
ExRNA is a peer-reviewed, open access journal that provides a platform for innovative research in the field of extracellular RNA. The journal covers a wide variety of RNAs in the extracellular environment, including miRNAs, siRNAs, piRNAs, lncRNAs and circRNAs. This journal aims to investigate the biological functions of extracellular RNAs, discover the fundamental principles about the mechanisms of extracellular RNA generation, uptake and transport and explore the potential for using extracellular RNAs in the clinic as therapeutic molecules or disease biomarkers. ExRNA encompasses all topics related to the biology of extracellular RNAs, including, but not limited to: Functional analysis of the biodistribution, structure and biological activity of extracellular RNAs Mechanistic studies on the production, transport, uptake, processing, modulation and modification of extracellular RNAs Translational studies to identify biomarkers and develop new tools, therapies and technologies to measure extracellular RNAs.